Identity theft: a legal study on phishing / Khadijah Ilyana Mahayudin…[et al.]. - Mahayudin, Khadijah Ilyana; Azman, Ayuni; Mustapa, Norainzan; Sulaiman, Salwa (2009)
In Malaysia, many internet users are getting more savvy by using the cyber space to do online transactions. However, the practicality of online transactions brings great harm to the users where their identity can be stolen and used by other third parties, which is also known as phishing. Phishing is a new cyber security issue in the current era of globalisation. This paper outlines the modus operandi of a typical phishing attack and provides a brief overview of the different types of phishing. The local Malaysia situation regarding phishing is also identified. The legal structures of Malaysia's and United States' phishing laws are also analysed to reveal that inadequacy of current legal framework in Malaysia is the main challenge in countering phishing schemes. Accordingly, prevention is always better than curb, especially in phishing matter. By the end of this paper, some best practices for users and the authorities are recommended to curb phishing schemes in Malaysia.